Enhanced production of Andrographolide from cell cultures of Andrographis paniculata by the elicitaion with Arachidonic acid - Ganeshkumar, Yamjala; Kavitha, Perala; Ramarao, Ajmera; Veeresham*, Ciddi (Indian Journal of Natural Products, 2019)
Background: Andrographis paniculata (Burm. F.) Wall ex. Nees, belonging to the family Acanthaceae produces a group of diterpene lactones, one of which is the pharmaceutically important andrographolide. Hypothesis:It is known to possess various important biological properties like hepatoptroective, anticancer, anti-HIV, anti inflammatory, etc. Method: The production of andrographolide in the cell suspension cultures of Andrographis paniculata by elicitation was investigated. Results: Arachidonic acid enhanced the andrographolide content in the suspension cultures of Andrographis paniculata. The maximum andrographolide production was found to 109.6 0.62% w/w over the control cell cultures 26.40.79% w/w with the addition of arachidonic acid (100 M) on day-7. Conclusion: This study could pave the way for establishing a continuous and higher production of andrographolide, which has an enormous pharmacological importance
Keywords: Andrographis paniculata; Arachidonic acid; suspension cultures; and HPLC